The struggles of reluctant workplace bloggers - Shafie, Latisha Asmaak; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2009)
Blogs act as knowledge repositories and personalize knowledge management within learning organizations.These knowledge repositories allow capturing and disseminating tacit knowledge which improve task implementations. However, workplace blogging is not popular among academicians as there are not many academicians blog about their working experiences. Thus, this study investigates the causes of workplace blogging resistance among four language lecturers at a local university in Malaysia. Interviews were conducted to identify the arguments over the resistance of workplace blogging .The findings of the study suggest several suggestions to overcome the resistance of workplace blogging.